2008
DOI: 10.1002/elan.200804337
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry and Electrocatalysis of Hemoglobin/ZnO‐Chitosan/nano‐Au Modified Glassy Carbon Electrode

Abstract: The highly efficient H 2 O 2 biosensor was fabricated on the basis of the complex films of hemoglobin (Hb), nano ZnO, chitosan (CHIT) dispersed solution and nano Au immobilized on glassy carbon electrode (GCE). Biocompatible ZnO-CHIT composition provided a suitable microenvironment to keep Hb bioactivity (Michaelis-Menten constant of 0.075 mmol L À1). The presence of nano Au in matrix could effectively enhance electron transfer between Hb and electrode. The electrochemical behaviors and effects of solution pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Biocompatible nanogold could further allow HRP to be immobilized with well-remained bioactivity in addition to increased loading amount. The prepared biosensor can achieve sensitive electrochemical response to H 2 O 2 at a potential of -0.2 V. Similar composites for enzyme immobilization was reported by Duan et al (Duan et al, 2008), but the composites were mixed by the solutions of ZnO/chitosan, Hb and gold. The as-prepared biosensor has a fast response to H 2 O 2 within 4 s and a detection limit of 0.097 µM.…”
Section: Introductionsupporting
confidence: 64%
“…Biocompatible nanogold could further allow HRP to be immobilized with well-remained bioactivity in addition to increased loading amount. The prepared biosensor can achieve sensitive electrochemical response to H 2 O 2 at a potential of -0.2 V. Similar composites for enzyme immobilization was reported by Duan et al (Duan et al, 2008), but the composites were mixed by the solutions of ZnO/chitosan, Hb and gold. The as-prepared biosensor has a fast response to H 2 O 2 within 4 s and a detection limit of 0.097 µM.…”
Section: Introductionsupporting
confidence: 64%
“…The developed biosensor displayed good performance for the detection of H 2 O 2 and NaNO 2 with a wide linear range of 1-410 and 10-2700 μM, respectively. Duan et al, (2008) prepared complex film containing of hemoglobin, nano ZnO, chitosan and nano Au to immobilized onto glassy carbon electrode for H 2 O 2 sensing. Chitosan improved the film forming ability to the substrate and presence of gold nanoparticles enhanced electrocatalytic performance such as reproducible high sensitivity, linearity (1.94 x 10 -7 -1.73 x 10 -3 mol L -1 ) and detection limit (9.7x 10 -8 mol L -1 ) of the fabricated bioelectrode.…”
Section: Hydrogen Peroxide Biosensorsmentioning
confidence: 99%
“…Sun et al reported electrochemistry of hemoglobin entrapped in a Nafion/nano-ZnO film on carbon ionic liquid electrode [28]. Duan and his co-workers developed a hydrogen peroxide biosensor based on the complex films of hemoglobin (Hb), nano ZnO, chitosan (CHIT) dispersed solution and nano Au immobilized on glassy carbon electrode (GCE) [29]. Kong [30].…”
Section: Introductionmentioning
confidence: 99%